(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The purpose of this article is to study and research methods and forms of gamification application in the educational process. The methodology of the article is based on the effective use of various modern pedagogical approaches accompanied by gaming technologies. The practical significance of the article lies in the possibility of further application of the main provisions and conclusions both in psychological and pedagogical activity and in the educational process.